Stomata leaves characteristics of sapindaceae family in malabar forest, Malang city - Endrik Nurrohman; Roimil Latifa; Samsun Hadi (UNIVERSITAS NEGERI PADANG, 2022)
Malabar forests are composed of various plant families, one of which is the Sapindaceae family. Differences in family, plant species, and environmental factors can affect the number of stomata and the size of plant cells. The purpose of this study was to explore the characteristics (number, density, type, shape, and size) of leaf stomata of plants of the Sapindaceae family in the Malabar forest of Malang City. This type of research is descriptive. The research was conducted in the Malabar City Forest of Malang City and the Biology Laboratory of the University of Muhammadiyah Malang. The study started from March 2021 to September 2021. The sampling technique was carried out using the cruising method. The method of collecting stomatal characteristics data using a light microscope and Scanning Electrone Microscope (SEM). The research data obtained were analyzed by descriptive statistics. The results showed that (1) there were 5 types of plants from the Sapindaceae family, there were variations in the size of the stomata parts of the Sapindaceae (2) family, the longest guard cell length was the stomata of the matoa leaf (22.4 m), the widest guard cell width was the matoa leaf (14.1 m). The longest pore length of rambutan leaves (15.8 m), and the widest pore width of longan leaf stomata (3.88 m), overall stomata are kidney-shaped, stomata types are anomocytic, paracytic, and cyclocytic, the highest stomata density kiara payung leaves (37.44 cells/mm2).Hutan malabar terdiri dari berbagai famili tumbuhan, salah satunya adalah famili Sapindaceae. Perbedaan famili, jenis tumbuhan, dan faktor lingkungan dapat mempengaruhi jumlah stomata dan ukuran sel tumbuhan. Tujuan penelitian ini adalah untuk mengetahui karakteristik (jumlah, kerapatan, jenis, bentuk, dan ukuran) stomata daun tumbuhan famili Sapindaceae di hutan Malabar Kota Malang. Jenis penelitian ini adalah deskriptif. Penelitian dilakukan di Hutan Kota Malabar Kota Malang dan Laboratorium Biologi Universitas Muhammadiyah Malang. Penelitian dimulai pada bulan Maret 2021 hingga September 2021. Teknik pengambilan sampel dilakukan dengan menggunakan metode cruising. Metode pengumpulan data karakteristik stomata menggunakan mikroskop cahaya dan Scanning Electrone Microscope (SEM). Data penelitian yang diperoleh dianalisis dengan statistik deskriptif. Hasil penelitian menunjukkan bahwa (1) terdapat 5 jenis tumbuhan dari famili Sapindaceae, terdapat variasi ukuran bagian stomata dari famili Sapindaceae (2) panjang sel penjaga yang paling panjang adalah stomata daun matoa (22,4 m), lebar sel penjaga terluas adalah daun matoa (14,1 m). Panjang pori terpanjang daun rambutan (15,8 m), dan lebar pori terlebar stomata daun kelengkeng (3,88 m), stomata keseluruhan berbentuk ginjal, tipe stomata anomositik, parasitik, dan siklositik, kerapatan stomata tertinggi daun kiara payung (37,44 sel/mm2).